EFFECT OF IRRIGATION SCHEDULING AT PHENOLOGICAL STAGES ON SEED YIELD AND WATER PRODUCTIVITY OF SAFFLOWER (Carthamus tinctorius L.) - S. NARENDER REDDY, G. JHANSI, J. PADMAJA, K. AVIL KUMAR AND (The Journal of Research, PJTSAU, 2019)
Safflower (Carthamus tinctorius L.) is one of humanity’s oldest crops cultivated in India mainly for oil, because of its richness in the unsaturated fatty acid i.e., linoleic acid (78%) from the seeds and a reddish dye from the flowers and is cultivated on a wide range of soils ranging from light soils to heavy soils under irrigated and rainfed conditions. India is the largest producer of safflower (1.13 lakh tonnes) in the world with highest acreage (1.4 lakh ha) but with an average productivity of only 638 kg ha-1. In Telangana, also it is grown in 7870 ha with productivity of 708 kg ha-1 (DoES, 2016). Poor crop management under inputstarved conditions is the most important reason for such low productivity.